Race, Gender, and Affirmative Action Attitudes in American and Canadian Universities - Katchanovski, Ivan; Nevitte, Neil; Rothman, Stanley (Canadian Journal of Higher Education, 2015)
Direct comparisons of American and Canadian faculty and students’ views concerning issues of race, gender, and affirmative action in higher education are rare. The 1999 North American Academic Study Survey provides a unique opportunity to analyze the role of national and positional factors in faculty and student attitudes towards race, gender, and affirmative action in the US and Canada. The findings indicate that national factors are more important than positional factors on many racial and affirmative-action issues. Differences between students and faculty are more pronounced than are cross-national variations on many gender-related issues.